Helmet Non-Invasive Ventilation for COVID-19 Patients (Helmet-COVID): study protocol for a multicentre randomised controlled trial - Yaseen M Arabi; Khalid Alghamdi; Eman Al Qasim; Fahad Al-Hameed; Haytham Tlayjeh; Mohammed Almaani; Zohair Al aseri; Sara Aldekhyl; Hasan M Al-Dorzi; Sheryl Ann Abdukahil; Mohammad Khulaif Al Harbi; Husain Al Haji; et al. (BMJ Open)
Introduction Non-invasive ventilation (NIV) delivered by helmet has been used for respiratory support of patients with acute hypoxaemic respiratory failure due to COVID-19 pneumonia. The aim of this study was to compare helmet NIV with usual care versus usual care alone to reduce mortality.Methods and analysis This is a multicentre, pragmatic, parallel randomised controlled trial that compares helmet NIV with usual care to usual care alone in a 1:1 ratio. A total of 320 patients will be enrolled in this study. The primary outcome is 28-day all-cause mortality. The primary outcome will be compared between the two study groups in the intention-to-treat and per-protocol cohorts. An interim analysis will be conducted for both safety and effectiveness.Ethics and dissemination Approvals are obtained from the institutional review boards of each participating institution. Our findings will be published in peer-reviewed journals and presented at relevant conferences and meetings.Trial registration number NCT04477668.